The desperadoes - Keyes, Evelyn, 1917-; Vidor, Charles, 1900-1959.; Scott, Randolph, 1898-1987.; Buchanan, Edgar, 1903-1979.; Brown, Harry Joe, 1893-1972.; Ford, Glenn, 1916-2006.; Carson, Robert, 1909-1983.; Trevor, Claire, 1909-2000.; Brand, Max, 1892-1944. (Culver City, Calif. : Columbia Pictures, 2005)
A reformed ex-outlaw (Ford) is framed for a bank robbery, his friend the sheriff (Scott) helps him escape, and together they bring the real robbers to justice.
Original story by Max Brand (Smiling desperado?).
Originally produced as a motion picture in 1943.
Director of photography, George Meehan ; film editor, Gene Haylick ; music, John Leipold.
Randolph Scott, Claire Trevor, Glenn Ford, Evelyn Keyes, Edgar Buchanan, Guinn (Big Boy) Williams, Raymond Walburn, Porter Hall.
Canadian Home Video Rating: PG.
DVD ; full screen presentation.
Keywords: Films for the hearing impaired; Western films; Feature films